2020
DOI: 10.4236/aid.2020.103002
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Oyo State Health Care Worker’s Knowledge, Attitude and Practice regarding Corona Virus Disease 2019 (COVID-19)

Abstract: Background: Health workers are at the front line of the COVID-19 outbreak response and as such are exposed to hazards that put them at risk of infection. Poor knowledge among HCWs and inadequate infection control practices may lead to the increased risk of COVID-19 nosocomial transmission. This study assessed the knowledge, attitude and practice of Oyo state health care workers on COVID-19 as part of emergency preparedness. Methods: A hospital based cross-sectional survey was conducted in selected health facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 5 publications
1
28
0
1
Order By: Relevance
“…A self-administered questionnaire ( Additional file ) was developed after a thorough review of the literature of previously published papers regarding SARS-COV, MERS-COV, and SARS-COV-2 and following WHO & CDC guidelines. We used 70% as a cut-off value for all the questionnaires based on the previously published studies [ 15 , 18 , 19 ]. It consisted of both multiple-choice questions and Likert scale items.…”
Section: Methodsmentioning
confidence: 99%
“…A self-administered questionnaire ( Additional file ) was developed after a thorough review of the literature of previously published papers regarding SARS-COV, MERS-COV, and SARS-COV-2 and following WHO & CDC guidelines. We used 70% as a cut-off value for all the questionnaires based on the previously published studies [ 15 , 18 , 19 ]. It consisted of both multiple-choice questions and Likert scale items.…”
Section: Methodsmentioning
confidence: 99%
“…The significant positive association between level of education and SARS-COV-2 infection knowledge score supports this speculation. A Chinese study has recently found a similar high knowledge rate among its participants (90%), indicating that the Chinese population is knowledgeable about SARS-COV-2 (9). However, according to Haque et al ., among 2045 respondents across Bangladesh, only 54.87% had good knowledge regarding COVID-19.…”
Section: Discussionmentioning
confidence: 91%
“…Unexpectedly, the practices of UAE healthcare workers as assessed by our study were suboptimal. A study performed in Nigeria reported low knowledge (78.6%) and poor attitude (64%) among healthcare workers (Ayinde et al, 2020 . More research is needed to investigate healthcare workers' competences and the knowledge necessary for their work in this challenging pandemic environment.…”
Section: Mental Health During the Pandemicmentioning
confidence: 99%
“…A self-administered questionnaire (additional le) was developed after a thorough review of the literature of previously published papers regarding SARS-COV, MERS-COV, and SARS-COV-2 and following WHO & CDC guidelines. We used 70% as a cut-off value for all the questionnaires based on the previously published studies [15,18,19]. It consisted of both multiple-choice questions and Likert scale items.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The Coronavirus Disease 2019 (COVID- 19) is recently identi ed as a fatal respiratory problem caused by the Novel Coronavirus subtype SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) [1]. On the last of December 2019, a cluster of pneumonia cases appeared in Wuhan, a highly populated city in Central China, where more than 11 million population reside [2].…”
Section: Introductionmentioning
confidence: 99%